Fluorescence energy transfer detection as a homogeneous DNA diagnostic method - Chen, Xiangning (The National Academy of Sciences of the USA, 1997)
A homogeneous DNA diagnostic assay based on template-directed primer extension detected by fluorescence resonance energy transfer, named template-directed dye-terminator incorporation (TDI) assay, has been developed for mutation detection and high throughput genome analysis. Here, we report the successful application of the TDI assay to detect mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, the human leukocyte antigen H (HLA-H) gene, and the receptor tyrosin kinase (RET) protooncogene that are associated with cystic fibrosis, hemochromatosis, and multiple endocrine neoplasia, type 2, respectively. Starting with total human DNA, the samples are amplified by the PCR followed by enzymatic degradation of excess primers and deoxyribonucleoside triphosphates before the primer extension reaction is performed. All these standardized steps are performed in the same tube, and the fluorescence changes are monitored in real time, making it a useful clinical DNA diagnostic method.